On the theory of generalized Toeplitz kernels - Berezansky, Yu.M.; Chernobai, О.В. (Український математичний журнал, 2000)
A new proof of the integral representation of the generalized Toeplitz kernels is given. This proof is based on the spectral theory of the corresponding differential operator that acts in the Hilbert space constructed from a kernel of this sort. A theorem on conditions that should be imposed on the kernel to guarantee the self-adjointness of the operator considered (i.e., the uniqueness of the measure in the representation) is proved. Наводиться нове доведення інтегрального зображення узагальнених ядер Тепліца. Це доведення базується на спектральній теорії відповідного диференціального оператора, що діє в гільбертовому просторі, побудованому за таким ядром. Одержано теорему про умови на ядро, які забезпечують самоспряженість цього оператора (тобто єдиність міри в зображенні)